Environmental and Economic Empowerment through Ecoprint Training for PKK Members - Ikhtiari, Kirana; Azis, Dian Eka Pusvita; Ningsih, Dina Surya; Sadham, Muhammad (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This community service activity aims to empower members of the Padanglampe Village PKK through training in the manufacture of ecoprint products made from local leaves as an effort to preserve the environment and create additional sources of income. The program is designed to improve technical skills, foster ecological awareness, and open up creative economic opportunities based on local potential. Research Design and Methodology: The methods used include socialization, entrepreneurship presentations, demonstrations of ecoprint techniques, hands-on practice in creating motifs on tote bags, and interactive discussions and marketing assistance. The activities are planned for August 2025 with a target of 15–20 PKK members. A participatory approach is used to ensure that participants truly master the skills. Findings and Discussion: This activity improved participants' understanding of the importance of environmentally friendly natural resource management and introduced ecoprint as an easy, economical production technique with high selling value. Participants demonstrated improved skills in producing tote bags with local leaf motifs and gained an understanding of simple branding and marketing processes for marketing environmentally friendly products. Implications: This program has practical implications for empowering rural women, particularly by creating green business opportunities that support sustainable development goals. From a managerial perspective, this program encourages the formation of community-based business groups and the development of market-ready creative products. The results of these activities are expected to strengthen the community's economic independence through sustainable ecoprint businesses.